Effect of Bimetallic Ni-Cr Catalysts for Steam-CO2 Reforming of Methane at High Pressure - Choi, Bong Kwan; Park, Yoon Hwa; Moon, Dong Ju; Park, Nam Cook; Kim, Young Chul (AMER SCIENTIFIC PUBLISHERS, 2015)
The present work was to carry out the development of high performance Ni-based catalyst for Steam-CO2 reforming of methane (SCR) which is suitable for Fischer-Tropsch synthesis of GTL-FPSO (floating, production, storage and offloading) process. The bimetallic Ni-Cr catalysts were prepared by co-impregnation method. The Ni and Cr loading amount were fixed at 12 wt% and 3 similar to 7 wt%, respectively. The catalytic reaction was conducted at 900 degrees C and 20 bar with reactant feed ratio of CH4:CO2:H2O:Ar = 1:0.8:1.3:1 and GHSV = 25,000 h(-1). The Cr-modified Ni/gamma-Al2O3 catalyst was characterized by BET surface area analysis, X-ray diffraction (XRD), H-2-temperature programmed reduction (TPR), H-2-chmisorption, CO2-temperature programmed desorption (TPD) and Transmission electron microscopy(TEM). To confirm the amount and type of the carbon deposition, the used catalysts were examined by Thermogravitic analysis (TGA) and Field emission-scanning microscopy/Energy dispersive X-ray analysis (FE-SEM/EDX). It was found that the bimetallic Ni-Cr catalyst exhibits highly dispersed Ni particles with strong metal-to-support interaction (SMSI) as well as excellent catalytic activity, resulting in the suppression of Ni sintering and carbon deposition.
Keywords: NICKEL-CATALYSTS; CARBON-DIOXIDE; SYNTHESIS GAS; STABILITY; SUPPORT; COKE